2012
DOI: 10.1136/bmjopen-2011-000343
|View full text |Cite
|
Sign up to set email alerts
|

A survey of early health effects of the Eyjafjallajökull 2010 eruption in Iceland: a population-based study

Abstract: ObjectiveTo estimate physical and mental health effects of the Eyjafjallajökull volcanic eruption on nearby residents.DesignCross-sectional study.SettingThe Icelandic volcano Eyjafjallajökull erupted on 14 April 2010. The eruption lasted for about 6 weeks and was explosive, ejecting some 8 million tons of fine particles into the atmosphere. Due to prevailing winds, the ash spread mostly to the south and south-east, first over the rural region to the south, later over the Atlantic Ocean and Europe, closing Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
2
21
2
2
Order By: Relevance
“…Sakurajima in Japan, over the long term (>30 years) experienced a relatively high mortality for respiratory diseases, which included lung cancer and COPD [11]. In 6–9 months after the end of Eyjafjallajökull eruption, residents from exposed areas reported several medical problems including increased wheezing, cough and phlegm, as well as eye and skin irritation [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakurajima in Japan, over the long term (>30 years) experienced a relatively high mortality for respiratory diseases, which included lung cancer and COPD [11]. In 6–9 months after the end of Eyjafjallajökull eruption, residents from exposed areas reported several medical problems including increased wheezing, cough and phlegm, as well as eye and skin irritation [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Adverse respiratory effects from exposure to volcanic ash have been documented during the eruption of Montserrat, British West Indies, in 1995 [7,8], and from Eyjafjallajökull volcano, Iceland, in 2010 [9,10]. In addition, repeated exposure to ash fall from Mount Sakurajima, Japan, was associated with increased mortality due to respiratory diseases including lung cancer and chronic obstructive pulmonary disease (COPD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported adverse respiratory symptoms following exposure to volcanic ash, both among children (Forbes, Jarvis, Potts, & Baxter, 2003; Naumova et al, 2007) and adults (Buist, Vollmer, Johnson, Bernstein, & Mccamant, 1986; Carlsen et al, 2012, 2012; Fano et al, 2006; Horton & McCaldin, 1964; Horwell & Baxter, 2006; Rojas-Ramos et al, 2001). Respiratory symptoms have also been found to be more common among both children and adults in high exposed areas, compared to non-exposed and low exposed areas (Carlsen et al, 2012; Forbes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We discuss in more detail: ash hazard assessment tools; communication tools available for the key sectors of public health, agriculture, and critical infrastructure; and However, very fine ash as PM2.5 and PM10 is a health hazard when it is readily suspended in the air by wind and traffic (Carlsen et al 2012a;Wilson et al 2012). Short-term effects commonly include irritation of the eyes and lung airways, and exacerbation of pre-existing asthma and chronic lung diseases (Horwell and Baxter 2006; see also www.ivhhn.org).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of respirable crystalline silica in some eruptions will cause much concern over the risk of silicosis, a chronic lung disease which is entirely preventable by adequate measures to reduce exposure in prolonged crises (e.g., Montserrat, 1995Montserrat, -2010. Affected communities can also experience psychological stress from disruption of livelihoods and other social impacts (Carlsen et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%